2002
DOI: 10.1128/mcb.22.15.5270-5280.2002
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Model of the Constitutive Androstane Receptor Defines Novel Interactions That Mediate Ligand-Independent Activity

Abstract: Unlike classical nuclear receptors that require ligand for transcriptional activity, the constitutive androstane receptor (CAR) is active in the absence of ligand. To determine the molecular contacts that underlie this constitutive activity, we created a three-dimensional model of CAR and verified critical structural features by mutational analysis. We found that the same motifs that facilitate ligand-dependent activity in classical receptors also mediated constitutive activity in CAR. This raises a critical q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
126
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(134 citation statements)
references
References 62 publications
(94 reference statements)
6
126
2
Order By: Relevance
“…A recent report on mouse CAR (34) indicated that an interaction of the negatively charged C terminus of helix 12 with the positively charged Lys-205 (Lys-195 in human CAR) in helix 4 may contribute to the stabilization of helix 12 (see Fig. 2B).…”
Section: Fig 1 Comparison Of Car and Vdr Signaling From Dr4-type Resmentioning
confidence: 99%
“…A recent report on mouse CAR (34) indicated that an interaction of the negatively charged C terminus of helix 12 with the positively charged Lys-205 (Lys-195 in human CAR) in helix 4 may contribute to the stabilization of helix 12 (see Fig. 2B).…”
Section: Fig 1 Comparison Of Car and Vdr Signaling From Dr4-type Resmentioning
confidence: 99%
“…The LXXLL-binding pocket can also be targeted by some corepressors. Like many other nuclear receptors, CAR is also bound and repressed by the following common corepressors: nuclear receptor corepressor 1 (NCoR1), NCoR2/SMRT, and DAX-1 (NR0B1) [53,54,57,62] . Collectively, the LXXLL-mediated direct interaction of CAR and its cofactors is very important for the activity of CAR.…”
Section: Modulators Of Car Activitymentioning
confidence: 99%
“…A number of coactivators have been found to physically interact with CAR [51] . The three members of p160 coactivators, SRC1, SRC2, and SRC3, as well as PGC1α have been reported to enhance the activity of CAR based on reporter gene assays [52][53][54][55][56][57] . The function of individual coactivators seems to be redundant, at least for the induction of mouse Cyp2b10 [58] .…”
Section: Modulators Of Car Activitymentioning
confidence: 99%
“…39 It would be worth exploring if it could interact with the charge clamp of NRs. 9,31,[40][41][42] Another interesting observation is the presence of a band at approximately 40 kDa at the western blot with anti-V5 Ab. Similar sized bands have been observed in our previous work, where a >40 kDa band was detected with western blot from mouse liver samples, with the use of a different Ab (Abcam ab467).…”
Section: Discussionmentioning
confidence: 99%